Heat transfer analysis of molten salt nitrates inside shell and tube heat exchanger with small round holed segmental baffles for concentrated solar power - Khaliquzzama, M. A.; Masuri, S. U.; Saidur, R.; Hairuddin, Abdul Aziz; Mohd Tahir, Suraya; Abd Malek, Norhazwani (Elsevier, 2025)
Investigating the heat transfer performance of molten salts for concentrated solar power (CSP) systems has posed significant challenges due to their high melting points, hence resulting in scarcity of such data. Additionally, high-pressure drops represent critical issues that need to be addressed. Conventional baffle designs contribute to these issues by causing excessive flow resistance while attempting to enhance heat transfer. Therefore, there is a need for an improved heat exchanger design that minimizes pressure drop while balancing the effective heat transfer performance. This study addresses these challenges by proposing a modified shell-and-tube heat exchanger (STHE) equipped with a novel baffle configuration featuring small round holes to enhance heat transfer efficiency and reduce pressure drop. A STHE was successfully modelled using ANSYS software for shell-side analysis, adhering to Tubular Exchanger Manufacturers Association (TEMA) standards which is widely used in industries. The model was validated through comparison with previously verified experimental data and CFD modelling. Three molten salts, namely Solar Salt, Hitec, and NaKCaNO3, were utilized as the heat transfer fluids in the STHE. With the original baffle design, the results showed that at mass flow rate of 2 kg/s, Solar Salt, Hitec, and NaKCaNO3 exhibited the highest pressure drops of 10.051, 10.128, and 9.651 kPa, respectively. The pressure drops were reduced to 5.820, 5.864, and 5.557 kPa, respectively, with the new 6 mm holed baffles. The modified baffles significantly reduced the pressure drop by up to 42 % compared to the original design, with only a minor reduction in the heat transfer coefficient, approximately 17 %. Further analysis revealed a remarkable efficiency improvement of up to 60 % in the modified STHE. The introduction of holes to the baffles substantially lowered the pumping power required for STHE operation. The efficiency improvement achieved through pressure drop reduction significantly outweighs the minor decrease in the heat transfer coefficient. Based on these results, it can be concluded that the heat transfer performance of molten salts in the new modified baffle design of STHE can further improve the efficiency of concentrated solar power (CSP) systems by optimizing thermal management and minimizing energy losses.